Layer-by-Layer Self-Assembled Dynamic Microcapsules (DynaMicCaps) with Polymer and Protein Shell-walls - N.F.D, AlDala’een; I.N, Sabri; W.N.K, Wan Mohamad; N., Alias; A.M, Ali; J., Shaikh Mohammed (2016)
Triggered delivery is one of the key areas of ongoing research in the field of drug delivery. To achieve triggered drug delivery, a variety of stimuli have been used including light, heat, ultrasound, magnetic field, pH, chemical species, etc. The Murphy group Bioinspired Materials Lab (BML) at UW-Madison has demonstrated biochemical ligand triggered drug delivery from PEG-CaM-PEG (PEG- Poly(ethylene glycol), CaM-Calmodulin) hydrogel slabs and microspheres based on the nanoscale conformational changes of hinge motion protein calmodulin (King, Mohammed, & Murphy, 2009; King, Pytel, Ng, & Murphy, 2010). To our knowledge, there has been no report of triggered drug delivery from dynamic microcapsules. This work presents fabrication (refer to Figure 1) and preliminary results of layer-by-layer (LbL) selfassembled dynamic microcapsules (DynaMicCaps) whose multilayered shell-walls are comprised of polyelectrolytes (polymers whose repeating units bear an electrolyte group) and CaM. It is anticipated that the triggered volume changes in the nano-engineered hollow microcarriers, DynaMicCaps, can be used in triggered drug release applications.